Sistem Pemesanan dan Pembayaran Menggunakan Teknologi Quick Response Code (QR Code) Berbasis Web pada Kedai Cangkir Gubug - Budi Hartono; Danang Danang (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The results of this study are in the form of a product, namely an android application, an ordering and payment system using Android-based QR Code technology. According to the research design, the research results go through two testing or validation processes, namely design validation by experts in this case expert lecturers in the computer field, and product validation by users.Validation is carried out using an assessment instrument in the form of a questionnaire or validation sheet. The questionnaire contains 10 questions that must be filled in with a value between 1 and 4. The total score will get a score of not good, enough, good, or very good. The final conclusion is a statement that the product must be replaced, can be used with many revisions, can be used with few revisions, or can be used without revision.The results of the design validation test by experts gave a total score of 37, included in the score indicator 31 n 40, namely